Judge Consideration of Religious Court Of Blora on Application of Married Dispensation - Siti Muzazanah Muzazanah; Akhmad Khisni; Rozihan Rozihan (Jurnal Daulat Hukum, 2019)
This study aims to know the factors increasing request for married dispensation, the judge in the consideration granted married dispensation and know the weaknesses of Marriage Act in court and in the implementation of solutions to reduce married dispensation, The method used normative juridical, namely legal research based on secondary data. This research approach using the approach of the case (case approach and qualitative approach. Regarding the data, the authors obtained data from interviews and literature study.These results indicate (1) Factors increasing request for married dispensation in the Religious Court of Blora is (a) Fearing the emergence of slander, (b) pregnant outside of marriage (2) Judge Consideration of Religion Court of Blora in granted married dispensation, based on consideration of three things namely (a) Administrative completeness, (b) there is no prohibition of marriage as contained in Article 8 of Act No. 1 of 1974 On Marriage, (c) the principle benefit (3) weakness of marriage Act in the execution of court and solutions for reduce married dispensation in the Religious Court of Blora. Lack of socialization to the relevant institutions make weak law marriage in the implementation of the court.Keywords: Judge Consideration; Religious Court; Married Dispensation.